2014
DOI: 10.3892/or.2014.3421
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the mTORC1 and STAT3 pathways promotes the malignant transformation of colitis in mice

Abstract: Chronic inflammation is an underlying risk factor for colorectal cancer. No direct evidence has proven that inflammation in the colon promotes carcinogenesis. STAT3 plays an important role in the development of colitis-associated colorectal cancer (CAC). There is crosstalk between the mammalian target of rapamycin complex 1 (mTORC1) and the STAT3 pathways. The aim of the present study was to confirm that colitis promotes CAC and if so, to explore the function of the STAT3 and mTORC1 pathways in CAC. C57BL/6 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Genetic variations in the JAK/STAT signaling pathway appear to influence CRC carcinogenesis . Interestingly, cross‐talk between STAT3 and the mammalian target of rapamycin complex 1, which controls anabolic cell growth and proliferation, can promote CRC in colitic mice …”
Section: Oxidative Stress–activated Signaling Pathways and Antioxidanmentioning
confidence: 99%
“…Genetic variations in the JAK/STAT signaling pathway appear to influence CRC carcinogenesis . Interestingly, cross‐talk between STAT3 and the mammalian target of rapamycin complex 1, which controls anabolic cell growth and proliferation, can promote CRC in colitic mice …”
Section: Oxidative Stress–activated Signaling Pathways and Antioxidanmentioning
confidence: 99%
“… 26 , 27 After being activated, STAT3 mediates the expression of a variety of genes, among which many are associated with cellular proliferation, apoptosis, and malignant transformation. 28 , 29 Furthermore, it has been confirmed that STAT3 plays a critical role in K-ras-dependent pancreatic carcinogenesis. 20 , 30 , 31 Therefore, STAT3 and its associated pathways are thought to be increasingly important in cancer research and as potential factors in clinical cancer treatment.…”
Section: Introductionmentioning
confidence: 97%
“…The process has been studied quite widely in murine models [36][37][38]. Evidence that p65 is closely allied to the viral oncoprotein v-Rel firstly establishes a link between NFjB and cancer [39].…”
Section: Discussionmentioning
confidence: 99%